Analysis of Entrepreneurial Orientation at Employees of PT. Pertamina Patra Niaga - Bandung Retail Sales Area - Cahyadi, Siska Swaradeta; Reni Wijayanti (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2023)
Entrepreneurial orientation is a concept that describes a person's attitude or behavior in strategic management and entrepreneurship that emphasizes the company's orientation towards innovation, risk-taking, and proactivity to maximize business opportunities. Therefore, it is crucial for a company, especially a state-owned company, to encourage employees to have an entrepreneurial orientation. The purpose of this study was to determine the Entrepreneurial Orientation of employees at PT Pertamina Patra Niaga - Bandung Retail Sales Area. The research was conducted using quantitative descriptive method. Respondents in the study were 40 people through questionnaires to employees of PT Pertamina Patra Niaga - Bandung Retail Sales Area. The results showed good results in the three dimensions of entrepreneurial orientation: innovativeness, proactiveness, and risk taking. This can be categorized as good because it is in accordance with the value interpretation